Does Nature Need Cities? Pollinators Reveal a Role for Cities in Wildlife Conservation - Derby Lewis, Abigail; Bouman, Mark J.; Winter, Alexis M.; Hasle, Aster F.; Stotz, Douglas F.; Johnston, Mark K.; Klinger, Karen R.; Rosenthal, Amy; Czarnecki, Craig A. (Frontiers in Ecology and Evolution, 2019)
It is well-established that cities need nature for critical ecosystem services—from storing carbon, to reducing temperatures, to mitigating stormwater—and there is growing momentum to seek out strategies for how these services can intersect with urban design and planning efforts. Social scientists and conservation planners increasingly point to urban residents' need to breathe fresh air, encounter the natural world, and have room to play. It is less obvious, perhaps, whether nature needs cities in order to thrive. The evidence from both urban planning and conservation planning is increasingly “yes.” As changes in land use and land cover sweep the planet, cities are becoming important refugia for certain wildlife populations. In recent years, urban planning has embraced the concept of “green infrastructure” as a way to embed green space across metropolitan landscapes to draw on the inherent benefits nature provides to cities, as well as to create habitat for wildlife. We explore this evolving view of cities and nature in the fields of urban and conservation planning. We argue the time is ripe to bring these worlds together, and, using our empirical work, establish that cities matter for monarch butterflies, other pollinators, and at-risk wildlife species.